“Not Today, Diabetes”: Using Blog Analysis to Understand Emotional Interactions and Support Among People With Type 1 Diabetes - Stuckey, Heather L.; Oser, Sean M.; Miller, Erin L.; Oser, Tamara K.; Peyrot, Mark; Sharma, Aditi (Frontiers in Clinical Diabetes and Healthcare, 2021)
The goal of this study is to understand how internet blogs are used by people with type 1 diabetes (T1D) to provide or exchange social support. A stratified, clustered proportionate probability sample of entries from 10 Internet blogs focusing on T1D was obtained. A random sample of 100 days generated 200 blogger posts and 1,606 commenter responses. Entries were coded using qualitative analysis software and analyzed thematically. Blogs were used as a dynamic, interactional form of emotional support from others who understood diabetes from personal experience; and as a source of sharing lived user experience of having diabetes, more often than as a way of communicating medical knowledge or facts about diabetes. Blog participation contributed to a sense of belonging for participants in the “Diabetes Online Community” where there was a shared culture. In conclusion, blogs provide unobtrusive access to the experiences of people with T1D that are driven by their interests rather than those of qualitative research interviewers or healthcare providers. In addition to permitting analysis of the way that participants use blogs to address their own personal wants and needs, blog data can serve as an inexpensive and unobtrusive method for studying topics of interests to researchers and healthcare providers.